TINJAUAN HUKUM ISLAM TERHADAP PENYELESAIAN PEMBIAYAAN MUD{A>RABAH PADA NASABAH YANG PAILIT DI PT. BNI SYARI’AH CABANG NGAGEL SURABAYA - Nur Azizah (Maliyah : Jurnal Hukum Bisnis Islam, 2015)
Completion of financing on customer mudarabah bankrupt due to factors beyond the mudarib error in BNI Shariah done by selling or execute a security object. Completion of the financing mudarabah led to the auction or sale of the collateral by taking the standard price between the price set by the government at market prices. While the banks sell at set prices that are considered good and have been taken into account by the bank. According to Islamic law, the settlement mudarabah financing to customers who have been bankrupt by the sale of the collateral is not allowed because it is not in accordance with Islamic law.